077. Ethanol Ablation as Therapeutic Options for Benign Thyroid Cyst: A Literature Review - Kallista, Annissa; Wibisana, IGN Gunawan (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p077, 2024)
Background : Minimally invasive management of symptomatic cystic thyroid nodules has become common practice. Ethanol ablation for benign thyroid cysts has been performed since 1990. Various consensus guidelines have been developed, but a more detailed review regarding the safety and outcomes of this procedure is still needed. This study aims to identify and summarize the indications, techniques, outcomes, and complications of ethanol ablation for benign thyroid cysts through a literature search and review using PubMed and EMBASE. Results: A database search using specific keywords identified a total of 134 titles. Screening of titles and abstracts with inclusion and exclusion criteria excluded 124 titles. After removing duplicates, checking full-text availability, and study eligibility, 7 studies met the criteria. Clinical evaluations, indications, techniques, outcomes, and complications were extracted from each study. Conclusion: Ethanol ablation (EA) is a safe, repeatable, cost-effective procedure that can be performed in an outpatient setting. It has transient side effects and complications, most of which resolve spontaneously. Thus, EA can be considered a first-line non-surgical treatment for benign thyroid cysts and predominantly cystic thyroid nodules (PCTN).